Impact of Obstructive Sleep Apnea on Neurological Recovery after Ischemic Stroke: A Prospective Study - Abdul Wahab; Wasim Tariq; Maimoona Siddiqui; Saad Ahmad (Indus Journal of Bioscience Research, 2025)
Objectives: In this investigation, the prevalence, clinical features, and impact of obstructive sleep apnea (OSA) on the prognosis of acute ischemic stroke patients were examined. Study design: Prospective Study. Settings: Department of Neurology, Shifa International Hospital, Islamabad. Study Duration: February 2025 to April 2025. Methods: Forty-nine patients with acute ischemic stroke were included. Lab findings, demographic data, and PSG features were collected. The modified Rankin Scale (mRS) was used to quantify the functional result, and the National Institutes of Health Stroke Scale (NIHSS) was utilized to gauge the extent of the initial neurologic loss. An poor prognosis was defined as an mRS ≥3 three months after the onset of acute ischemic stroke. Multivariate logistic regression was employed to assess the correlation between OSA severity and functional outcome. Results: OSA [apnea-hypopnea index (AHI)≥5/h] was present in 43 (87.8%) of the 49 patients who suffered an acute ischemic stroke. Of the patients, 13 (26.5%) had severe OSA, 16 (32.7%) had moderate OSA, and 14 (28.6%) had mild OSA. OSA-related factors, such as oxygen desaturation index (ODI) and AHI, were linked to poor clinical outcomes three months after stroke (mRS ≥3), according to univariate logistic regression. After controlling for age and initial NIHSS, multivariate logistic regression analysis showed that a rise in AHI and ODI was linked to a poor functional outcome three months following a stroke. Conclusions: Poor functional outcomes are linked to OSA in patients who have had an acute ischemic stroke.